Increase Production Secondary Substances in Hedera helix L. Callus by Abiotic Elicitor (Journal of the College of Basic Education, 2026)
Ivy (Hedera helix L.) leaves contain variety of secondary substances that have therapeutic effects on many diseases. Naturally these substances are low concentrations and high cost, researchers have turned to a new method aimed to increase production in callus culture from leaf as explant by using a safe elicitor polyethylene glycol (PEG) at concentrations (0, 20, 30, 40, and 50)%. This experiment was carried out in tissue culture laboratory at College of Science, University of Mustansiriyah in a completely randomized design (CRD) with three replicates to each concentration. The results showed that there was a significant effect of PEG on the fresh weight and highest value was achieved at 20%. Based on the high-performance liquid chromatography (HPLC) analysis of the alcoholic callus extract shows that significant increase in flavonoids (Nicotiflorin, Quercetin, and Kaempferol) and terpeniods (Hederacoside C, α-Hederin, Hederacoside B, and Hederacoside D). The highest values of flavonoids and terpeniods were achieved the highest average at 50% of PEG. In general, the conclusion of the study indicates that the PEG elicited the callus to medicinal compounds production.